KITE STRING INJURY: OUR EXPERIENCE AT A TERIARY CARE CENTER (Indian Journal of Applied-Basic Medical Sciences, 2020)
BACKGROUND: Kite flying is a popular sport in many cultures around the world. In India, Makar Sankranti or Uttarayan is celebrated on 14th January. This festival is dedicated to the ‘Sun God’, ‘Surya’ in Hindu religion. These kite festivals include a game of kite fighting, in which participants attempt to use their kite to cut the string of a rival kite. Injuries related to kite flying commonly range from mild injuries to severe disability and death; and may manifest with varied clinical presentations with chemical, metallic strings. Kite flying is very common in India and we feel that trauma caused by the kite thread is grossly underreported. OBSERVATIONS AND RESULTS: In our study, there were total 40 cases reported during the period of 2 months, December and January. 39(97.5%) of cases were reported during 13th to 15th January and 1(2.5%) case in December 2018. 35(87.5%) were male patients and 5(12.5%) female patients. 4(10%) patients were below 12 years and the rest were above 12 years. Protective measures wise, 26(65%) patients did not use any protective device out of these 10(38.5%) had severe injuries. While 5(12.5%) of them used either muffler or dupatta around their neck, 2(50%) patients had severe injury. 6(15%) patients used helmets and 3(7.5%) patients used wire frame in front of the vehicle; none of them had severe injuries. 12(30%) of the 40 patients had severe injuries involving neck muscles, major vessels and upper airway compromise, sclera, conjunctiva, eyelid, out of which 3(7.5%) patients required tracheostomy as a lifesaving procedure of which one succumbed to death. Out of 40 patients, 1(2.5%) patient succumbed to injuries and 39(97.5%) survived. CONCLUSION: A seemingly harmless game of kite flying can cause grievous harm even death not only to the flyers but also to innocent others. This study highlights that protection such as helmet, muffler, dupatta around the neck can reduce the grievousness of injury over head and neck but not give complete protection from innocent looking kite threads. Awareness programmes regarding the safety measures to protect oneself from grievous injuries can be conducted using pictorial depictions, minimal usage of two wheelers during those peak hours of kite flying can reduce the incidence of casualties caused by killer manja. Banning of Chinese threads and glass coatings on the threads by government can also reduce injuries.
Keywords: Kite string; head and neck injuries